2016
DOI: 10.4269/ajtmh.15-0538
|View full text |Cite
|
Sign up to set email alerts
|

Surveying the Knowledge and Practices of Health Professionals in China, India, Iran, and Mexico on Treating Tuberculosis

Abstract: Research evidence continues to reveal findings important for health professionals' clinical practices, yet it is not consistently disseminated to those who can use it. The resulting deficits in knowledge and service provision may be especially pronounced in low- and middle-income countries that have greater resource constraints. Tuberculosis treatment is an important area for assessing professionals' knowledge and practices because of the effectiveness of existing treatments and recognized gaps in professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 105 publications
2
13
2
3
Order By: Relevance
“…In addition to improving quality of care in both public and private sectors, there is a need for community-based interventions to educate the public about how TB is spread and encourage early care seeking. An extensive literature indicates persistence of poor knowledge about spread and control of TB infection, both among health providers25–28 and among the patients 29–31. Despite India’s economic progress, stigma around TB seems to persist, with nearly 15% of men and women indicating that they would prefer to keep their TB status a secret, which is a marginal improvement from about 17% of men and women responding so almost a decade back in the earlier round of NFHS (NFHS-3, 2005–2006) 32.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to improving quality of care in both public and private sectors, there is a need for community-based interventions to educate the public about how TB is spread and encourage early care seeking. An extensive literature indicates persistence of poor knowledge about spread and control of TB infection, both among health providers25–28 and among the patients 29–31. Despite India’s economic progress, stigma around TB seems to persist, with nearly 15% of men and women indicating that they would prefer to keep their TB status a secret, which is a marginal improvement from about 17% of men and women responding so almost a decade back in the earlier round of NFHS (NFHS-3, 2005–2006) 32.…”
Section: Discussionmentioning
confidence: 99%
“…This result might be related to the amount of curriculum time devoted to TB and the number of TB patients seen by the students [ 20 , 23 ]. However, Hoffman [ 24 ] reported in 2016 that even among health professionals, a significant gap remained for improvement of knowledge and practices regarding TB.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge gaps as well as poor attitudes and practices in relation to infection prevention and control, including TB control, have been documented among HCWs working in Hajj [5]. Numerous reports worldwide found that HCWs have important knowledge gaps in relation to TB diagnosis, treatment and infection prevention and control; have some negative attitudes and stigma connected with the disease; and engage in poor practices, all of which contribute to their increased risk of infection and negative impacts on patients and the community [723]. However, no study specifically examined KAP of HCWs working in Hajj in relation to TB.…”
Section: Introductionmentioning
confidence: 99%